Effectiveness of a Community-Based First Aid Education Program on Choking for Laypersons in Surabaya, Indonesia: A Quasi-Experimental Study - Tia Maya Affrita; Fitria Kusuma; Endang Susanti Warasanti; Tanggono, Aninda (HM Publisher, 2024)
Choking is a leading cause of accidental death, particularly among children and the elderly. Prompt first aid, especially the Heimlich maneuver, is crucial in preventing fatalities. This study aimed to evaluate the effectiveness of a community-based first aid education program on choking in Surabaya, Indonesia. A quasi-experimental, pre-post design was implemented in Surabaya. Participants were recruited from various community settings (workplaces and community centers). The intervention group received a comprehensive first aid education program on choking, while the control group received standard health education. Knowledge and skills related to choking first aid were assessed before and after the intervention. A total of 350 participants completed the study (175 per group). The intervention group demonstrated a significant improvement in knowledge (p < 0.001) and skills (p < 0.001) related to choking first aid compared to the control group. Additionally, the intervention group reported increased confidence in their ability to respond to choking emergencies. The community-based first aid education program significantly enhanced knowledge, skills, and confidence in choking first aid among laypersons in Surabaya. Such programs should be considered as a public health strategy to reduce choking-related morbidity and mortality.